(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study was to measure the urinary mercury concentration in students after chewing gum for certain period of time. Sixteen students from faculty of dentistry had used chewing gum for five hours a day for seven days. Urine sample collected 24 h before and after the experimental time. Total mercury in urine (U-Hg) was determined by means of inductively coupled plasma mass spectrometry (ICPMS). t-test was used for the comparison of mercury before and after chewing gum. A non significant difference was found after chewing than before chewing gum.